1996
DOI: 10.1103/physrevb.53.11451
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in porous Vycor glass

Abstract: Hydrogen in porous Vycor glass ͑pore radius R p ϭ3.0 nm͒ has been investigated with a torsional oscillator technique at 7.5 K рTр 22 K. H 2 molecules which are adsorbed in Vycor at TϾT 3 (T 3 , triple point of bulk H 2 ) leave the Vycor when decreasing the temperature to below a characteristic value T c рT 3 ; T c depends on the amount of H 2 in the Vycor. This interpretation of the data is supported by simultaneous measurements of the H 2 vapor pressure. A similar phenomenon is observed with a capacitor fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Following this line of thinking many experimental and theoretical studies have focused on the characterization and analysis of p-H 2 films adsorbed on different substrates. [5][6][7][8] For instance, two-dimensional hydrogen has been observed to freeze at temperatures around 5 K when placed onto an exfoliated graphite plate. 9 Also, it has been experimentally shown that small para-hydrogen clusters immersed in 4 He droplets exhibit superfluidlike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Following this line of thinking many experimental and theoretical studies have focused on the characterization and analysis of p-H 2 films adsorbed on different substrates. [5][6][7][8] For instance, two-dimensional hydrogen has been observed to freeze at temperatures around 5 K when placed onto an exfoliated graphite plate. 9 Also, it has been experimentally shown that small para-hydrogen clusters immersed in 4 He droplets exhibit superfluidlike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is due the depth of the attractive well of the potential between two Hydrogen molecules, significantly greater than that between two Helium atoms. Several, attempts have been made 3,4,5,6 to supercool bulk liquid p-H 2 , but the search for SF (in the bulk) has so far not met with success.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made [10]- [13] to supercool bulk liquid p-H 2 , but the search for a SF phase has so far not met with success. Confinement and reduction of dimensionality are widely regarded as plausible avenues to the stabilization of a liquid phase of p-H 2 at temperatures sufficiently low, such that a SF transition may be observed.…”
mentioning
confidence: 99%